STUDI SISTEM PROTEKSI LINE CURRENT DIFFERENTIAL RELAY PADA SALURAN TRANSMISI 150 KV - N. B. Dharmawan; W. G. Ariastina; A. A. N. Amrita (Program Studi Teknik Elektro UNUD, 2020)
Increasing electricity demand in South Bali requires a reliable electrical system. Reliableelectrical systems can be achieved in various ways, one of which is the replacement of highvoltage overhead line to high voltage underground cable. The replacement high voltageoverhead line to high voltage underground cable requires adjustment of the protection system.The previous main protection system used in high voltage overhead line is distance relay, whilethe protection system for the new transmission network is line current differential relay. Thepurpose of this study is to analyze GIS Pesanggaran to GI Nusa Dua transmission line’sprotection system. The covered in this analysis is to power flow analysis simulation, 3 phaseshort circuit simulation, relays setting calculation and testing the relays setting.The power flowsimulation showed that the current at peak load from GIS Pesanggaran to GI Nusa Dua is 337A. The 3 phase short circuit simulation showed that the largest short circuit, if a fault occurs onthe GI Nusa Dua of 9.54 kA. The relays setting calcullation showed that of 0,2 A with 20 %slope for Is1 and 2 A with 150% slope for Is2. The results showed that the relays setting hasworked properly.